2005
DOI: 10.1111/j.1365-2958.2005.04916.x
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature‐induced insecticidal activity of Yersinia enterocolitica

Abstract: SummaryThe insecticidal toxin complexes (Tcs) are produced by several Enterobacteriaceae associated with insects, such as Photorhabdus luminescens , Serratia entomophila and Xenorhabdus nematophilus. Genome sequences revealed tc -like genes in Yersinia spp., but insecticidal activity of this genus associated with the toxins has not been described. Through the search for genes upregulated at low growth temperatures in Yersinia enterocolitica strain W22703, a genomic island of 19 kb termed tc -PAI Ye with homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 37 publications
5
82
0
Order By: Relevance
“…Although the phage has integrated at the same chromosomal location and thus could be considered orthologous, there are differences within the prophage. As phages are mobile elements, the genome locus might also simply present an integrational The first is the tc pathogenicity island (PAI) which confers toxicity against insects to Y. enterocolitica (Bresolin, et al, 2006a;Fuchs, et al, 2008). Except for one strain, these have not been found in the non-or high-pathogenic BTs.…”
Section: Y Enterocoliticamentioning
confidence: 99%
“…Although the phage has integrated at the same chromosomal location and thus could be considered orthologous, there are differences within the prophage. As phages are mobile elements, the genome locus might also simply present an integrational The first is the tc pathogenicity island (PAI) which confers toxicity against insects to Y. enterocolitica (Bresolin, et al, 2006a;Fuchs, et al, 2008). Except for one strain, these have not been found in the non-or high-pathogenic BTs.…”
Section: Y Enterocoliticamentioning
confidence: 99%
“…Due to the absence of flaA in two Y. enterocolitica strains, as well as the wild-type-like motility of several double mutants in a flaA 2 background, the role of this additional flagellar subunit gene remains unclear. The distribution pattern of Flag-2 is similar to that of other genome domains, such as the insecticidal pathogenicity island tc-PAI Ye (Bresolin et al, 2006b), indicating an evolutionary split of biotypes 1A and 1B from biotypes 2-5. We suggest that biotypes 2-5, but not 1A or 1B, use insects as transmission vectors, and that Flag-2 genes contribute to the fitness of pathogenic Y. enterocolitica outside their mammalian hosts, possibly by increasing the chance of encountering an invertebrate host.…”
Section: Discussionmentioning
confidence: 61%
“…Swine have been identified as a major source of human infection (Bottone, 1997;Fredriksson-Ahomaa et al, 2006). A multiphasic life cycle, which comprises a free-living phase, a potential insect-associated phase and a host-dependent phase, may be characteristic of biotypes 2-4 of this pathogen (Bresolin et al, 2006b). …”
Section: Introductionmentioning
confidence: 99%
“…Close inspection of the Y. pestis genome shows that some of the tc homologues are not intact, however recent microarray analysis have revealed that these toxin complexes are conserved and potentially functional in Y. pseudotuberculosis and Y. enterocolitica (Bresolin et al, 2006;Erickson et al, 2007;Hinchliffe et al, 2003;Stabler et al, 2003). tc homologues of tcaA, tcaB, tcaC and tccC are activated at low growth temperatures in Y. enterocolitica strains of biovars 2, 3 and 4 (Bresolin et al, 2006). The insecticidal activity of Yersinia Tc is a matter of controversy.…”
Section: Insects As Vectors For a Number Of Disease-causing Bacteriamentioning
confidence: 99%
“…These genes are homologues of the tc insecticidal-toxin complexes found in entomopathogenic Enterobacteriaceae such as P. luminescens, S. entomophila and X. nematophilus Hurst et al, 2000;Hurst et al, 2007b;Joo Lee et al, 2004;Sulakvelidze, 2000;Waterfield et al, 2007;Waterfield et al, 2001). Close inspection of the Y. pestis genome shows that some of the tc homologues are not intact, however recent microarray analysis have revealed that these toxin complexes are conserved and potentially functional in Y. pseudotuberculosis and Y. enterocolitica (Bresolin et al, 2006;Erickson et al, 2007;Hinchliffe et al, 2003;Stabler et al, 2003). tc homologues of tcaA, tcaB, tcaC and tccC are activated at low growth temperatures in Y. enterocolitica strains of biovars 2, 3 and 4 (Bresolin et al, 2006).…”
Section: Insects As Vectors For a Number Of Disease-causing Bacteriamentioning
confidence: 99%